Avian influenza overview May – September 2021. (21st January 2022) - ,; ,; Adlhoch, Cornelia; Fusaro, Alice; Gonzales, José L; Kuiken, Thijs; Marangon, Stefano; Niqueux, Éric; Staubach, Christoph; Terregino, Calogero; Aznar, Inma; Muñoz Guajardo, Irene; et al.
Abstract: The 2020–2021 avian influenza epidemic with a total of 3, 777 reported highly pathogenic avian influenza (HPAI) detections and approximately 22, 900, 000 affected poultry birds in 31 European Countries appears to be one of the largest HPAI epidemics that has ever occurred in Europe. Between 15 May and 15 September 2021, 162 HPAI virus detections were reported in 17 EU/EEA countries and the UK in poultry (51), in wild (91) and captive birds (20). The detections in poultry were mainly reported by Kosovo (20), Poland (17) and Albania (6). HPAI virus was detected during the summer months in resident wild bird populations mainly in northern Europe. The data presented in this report indicates that HPAI virus is still circulating in domestic and wild bird populations in some European countries and that the epidemic is not over yet. Based on these observations, it appears that the persistence of HPAI A(H5) in Europe continues to pose a risk of further virus incursions in domestic bird populations. Furthermore, during summer, HPAI viruses were detected in poultry and several wild bird species in areas in Russia that are linked to key migration areas of wild waterbirds; this is of concern due to the possible introduction and spread of novel virus strains via wild birds migrating to the EU countries during the autumn from the eastern breeding to the overwintering sites. Nineteen different virus genotypes have been identified so far in Europe and Central Asia since July 2020, confirming a high propensity for this virus to undergo reassortment events. Since the last report, 15 human infections due to A(H5N6) HPAI and five human cases due to A(H9N2) low pathogenic avian influenza (LPAI) virus have been reported from China. Some of these cases were caused by a virus with an HA gene closely related to the A(H5) viruses circulating in Europe. The viruses characterised to date retain a preference for avian‐type receptors; however, the reports of transmission events of A(H5) viruses to mammals and humans in Russia, as well as the recent A(H5N6) human cases in China may indicate a continuous risk of these viruses adapting to mammals. The risk of infection for the general population in the EU/EEA is assessed as very low, and for occupationally exposed people low, with large uncertainty due to the high diversity of circulating viruses in the bird populations.